Significant association between host transcriptome‐derived HPV oncogene E6* influence score and carcinogenic pathways, tumor size, and survival in head and neck cancer. Issue 9 (14th May 2020) - Qin, Tingting; Koneva, Lada A.; Liu, Yidan; Zhang, Yanxiao; Arthur, Anna E.; Zarins, Katie R.; Carey, Thomas E; Chepeha, Douglas; Wolf, Gregory T.; Rozek, Laura S.; Sartor, Maureen A.
Abstract: Background: Human papillomavirus (HPV) oncogenes E6, E7, and shorter isoforms of E6 (E6*) are known carcinogenic factors in head and neck squamous cell carcinoma (HNSCC). Little is known regarding E6* functions. Methods: We analyzed RNA‐seq data from 68 HNSCC HPV type 16‐positive tumors to determine host genes and pathways associated with E6+E7 expression (E6E7) or the percent of full‐length E6 (E6%FL). Influence scores of E6E7 and E6%FL were used to test for associations with clinical variables. Results: For E6E7, we recapitulated all major known affected pathways and revealed additional pathways. E6%FL was found to affect mitochondrial processes, and E6%FL influence score was significantly associated with overall survival and tumor size. Conclusions: HPV E6E7 and E6* result in extensive, dose‐dependent compensatory effects and dysregulation of key cancer pathways. The switch from E6 to E6* promotes oxidative phosphorylation, larger tumor size, and worse prognosis, potentially serving as a prognostic factor for HPV‐positive HNSCC.